The Influence of “Ubrug” Sociodrama Technique toward Students Self-Efficacy - Permatasari, Siska; Rahmawati; Dalimunthe, Raudah Zaimah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
The study's purpose is to know the effects of the 'ubrug' sociodrama technique 'on a student's self-efficacy and the effectiveness or failure of a given technique. This type of research is a pre-experimental study using one group pre-post test design. The population taken as many as 112 students with the characteristics of class IX students (a, b, and c), aged 14-16 years, have low self-efficacy with a lack of self-confidence and slightly more closed behavior, are willing to take the time to fill out the questionnaire given, and students must be committed to the